Hubungan Komitmen Organisasional dengan Kinerja Pegawai pada Sekretariat Daerah Kabupaten Tanah Datar - Iis Syafrianti; Sufyarma Marsidin; Irsyad Irsyad (Journal of Educational Administration and Leadership, 2020)
This reasearch aimed to describe organizational commitment related to the performance of employees at the Regional Secretariat of Tanah Datar, to know the organizational commitment of employees at the Regional Secretariat Tanah Datar and to know the performance of employees at the Regional Secretariat of Tanah Datar. The type of this research is correlational research with quantitative approach, population in research is all employees at Regional Secretariat of Tanah Datar which amounts to 104 people. The samples were taken based on Slovin using proportional stratified random sampling technique and obtained 51 samples. The instrument is a Likert scale questionnaire with five choices of answers that have been tested for validity and reliability. Data analysis used in this research is correlation coefficient test and t test with SPSS 16.0. From result of research indicate that there is significant correlation between organizational commitment variable with employee performance. The level of performance at the Regional Secretariat of Tanah Datar Regency is Quite High. While the organizational commitment variable is in the Quite High